Assessment of republic act 10963: The 2017 tax reform for acceleration and inclusion - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2018)
Despite various reform efforts over the years, the tax system in the Philippines continues to suffer from chronic weaknesses. Tax rates are high relative to the country's ASEAN neighbors, yet revenue productivity remains low. Filipino individual taxpayers are overburdened by personal income tax brackets that have not been indexed to inflation, resulting in bracket creep. The real value of excise tax rates on petroleum products have likewise been eroded by inflation, and the schedule is characterized by a number of exemptions and rates that are low by international standards. The value-added tax base has narrowed from excessive exemptions.Package 1 of the Duterte administration's tax reform program was enacted into law as RA 10963, otherwise known as the "Tax Reform for Acceleration and Inclusion" (TRAIN) Act. It amended structure of the personal income tax, value-added tax, and excise tax on petroleum products, cigarettes, automobiles, sweetened beverages, coal and coke, and mineral products. While the RA 10963 reduced the personal income tax liability of both compensation income earners and the self-employed and professionals, it also raised the excise taxes on the aforementioned products and broadened the coverage of the VAT. This paper provides an assessment of the RA 10963's implications on the economic incentives in affected sectors, national government revenues, distribution of tax burden across income groups, and likely impact on tax compliance.
Keywords: 330; tax reform; personal income tax; value-added tax; excise tax; sugar-sweetened beverages; tax progressivity/regressivity; Reynolds-Smolensky index; tax compliance; negative externality